Analisis Identifikasi Bahaya K3 dengan Metode HIRARC pada Unit Recycle Industri Tekstil Nonwoven - Raihan Januar Anggoro; Syadzadhiya Qothrunada Z. Nisa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Occupational Safety and Health (K3) is a program created by employees and employers as an effort to prevent work-related accidents and diseases by identifying things that have the potential to cause work-related accidents and diseases as well as anticipatory actions in the event of work-related accidents and diseases. The method used in this study is the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. This method consists of a series of OSH implementations which include hazard identification, risk assessment, and determination of control measures based on the data collected. The results of the risk assessment are used as a reference in the implementation of risk control. This study uses surveys and interviews to collect data to identify potential hazards in the recycle unit, risk assessment and risk control are carried out by observing and identifying as well as interviewing workers and company owners in the recycle unit. From the results of the identification of the recycle unit that has been carried out, there are several potential hazards that can be identified and the risk assessment and risk categories in the recycle unit can be identified. Based on the results of the study, there were 31 potential hazards in the recycle unit, of which 19.3% were in the low risk category, 61.2% were in the moderate risk category, and 16.6% were in the high risk category. Identification of hazards carried out in the work process in the recycle unit, potential hazards contained in the recycle unit, namely; exposed wires, inhalation of dust, exposure to noise, exposure to hot engines, and exposure to hot polymer spills.